Morbidity and mortality pattern of intramural and extramural neonate: a prospective observational study - Meshram, Rajkumar M.; Jain, Dipty L.; Apte, Mohini U.; Denge, Abhishek (International Journal of Contemporary Pediatrics, 2021)
Background: Neonatal period carries higher risk of death inspite of advances in perinatal and neonatal services. The objective of the study was to assess the morbidity/mortality pattern of intramural and extramural neonates. Methods: Prospective observational study was undertaken on all intramural and extramural neonates who fulfill the inclusion criteria at a tertiary institute for one year. Morbidity and mortality patterns were analyzed. Results: A total 1770 intramural and 997 extramural neonates required admission during the study period. Mortality rate in intramural neonate was 22.26% while in extramural neonate was 28.79%. The male to female ratio was 1.27:1 in intramural while 1.3:1 in extramural neonates. Preterm neonates with extremely/very low birth weight were predominant in intramural group and term neonates in extramural group (p<0.001). Maternal illness during pregnancy were significantly more in mothers of extramural neonates compared to that of intramural neonates (p<0.001). Lethargy and hypothermia was significantly more in extramural group (p<0.001) while respiratory distress was significantly higher in intramural group (p=0.01). The leading causes of admission in intramural neonates was prematurity with respiratory distress syndrome (31.64%) while sepsis (37.01%) in extramural group of neonates. Preterm birth complication (51.52%) was the common cause of mortality in intramural neonates while sepsis (42.16%) in extramural neonates. Conclusions: Sepsis is the most common cause of morbidity/mortality in extramural neonates while prematurity and its complication in intramural neonates.